The development of a decision support model for the picking, staging, combining and loading activities in the grocery distribution warehouse of a large fast moving consumer goods retailer - Van Niekerk, W.W. (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2017.